Influences of Individual Differences, Internet Communication Motives, and Internet Usage on Social Well-Being and Satisfaction - Pornsakulvanich, Vikanda (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The present study examines the influence of dispositions (i.e., unwillingness to communicate, locus of control), internet communication motives, and the amount of internet use on social well-being and satisfaction. There are 485 participants in this study. The findings indicate the relationships among dispositions, internet communication motives, internet use, social well-being, and satisfaction. Specifically, the locus of control and interpersonal communication motives are the significant predictors of both social well-being and satisfaction. Those who are internal-looking or believe that they can control what happens in their lives prefer using internet for information searching and sharing and interpersonal communication and may have positive social well-being. Moreover, those who are external-looking or believe that their lives are shaped by other factors beyond their control prefer using internet for interpersonal communication and social networking and may feel satisfied with their online communication.